The Use of CEUS in the Diagnosis of Retinal/Choroidal Detachment and Associated Intraocular Masses – Preliminary Investigation in Patients with Equivocal Findings at Conventional Ultrasound - Bertolotto, M.; Serafini, G.; Sconfienza, L. M.; Lacelli, F.; Cavallaro, M.; Coslovich, A.; Tognetto, D.; Cova, M. A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: To investigate whether contrast-enhanced ultrasound (CEUS) may help to diagnose retinal/choroidal detachment and may help to differentiate intraocular lumps in cases with equivocal features on conventional grayscale and Doppler modes. Materials and Methods: The institutional review board approved this retrospective study. The need for informed consent was waived. A computerized data search was performed in the database of our institution for patients with vitreous hemorrhage who underwent CEUS of the eye to assess retinal/choroidal detachment and/or associated masses. This process yielded a total of 31 patients (18 men, 13 women, age range: 39 – 88 years) in whom CEUS was performed because the findings on conventional grayscale and Doppler modes were equivocal. CEUS was performed using low acoustic power contrast-specific modes. A 2.4 – 4.8 mL bolus of SonoVue was injected, followed by a saline flush. All examinations were digitally recorded for retrospective analysis. Confirmation of CEUS findings was obtained at surgery (n = 20) or with binocular indirect fundoscopy performed after clearance of the ocular media (n = 11). Two readers with different levels of ultrasound experience independently reviewed the imaging features. A five-degree scale ranging from definitely absent (score 1) to definitely present (score 5) was used to assess the presence or absence of retinal/choroidal detachment on conventional ultrasound modes alone and with the addition of CEUS. ROC curve analysis was performed to assess the diagnostic accuracy of both methods. The inter-reader agreement was also evaluated. In patients with associated intraocular lumps, conventional Doppler modes and CEUS were used to differentiate non-tumor masses from tumor masses. Results: According to the reference standard, 13 patients had retinal detachment, 4 had choroidal detachment, and 3 had both retinal and choroidal detachment. There were 8 associated intraocular lumps (4 subretinal hemorrhages, 3 malignant melanomas, 1 metastasis). The inter-reader agreement was good (K = 0.644) and very good (K = 0.833) for conventional modes and CEUS, respectively. The diagnostic performance of CEUS was high for both readers (area ± standard error under the ROC curve: 0.966 ± 0.031 and 0.900 ± 0.055 for readers 1 and 2, respectively). There were 2 false-positive results and 1 false-negative result in patients with proliferative diabetic retinopathy. CEUS was effective in differentiating subretinal hemorrhage from hypovascular tumors. Conclusion: CEUS can be used as a problem-solving technique when conventional ultrasound modes are not diagnostic for retinal/choroidal detachment and when intraocular lumps cannot be characterized as tumor or non-tumor masses on conventional modes. The evaluation of patients with proliferative diabetic retinopathy, however, may be problematic.
Keywords: eye, retinal detachment; eye, ultrasound; eye, CEUS